Mesial temporal sclerosis - Deshpande, Sheetal; Kashyap, Prashant; Dave, Dhaval; Mukherji, Anannya (International Journal of Research in Medical Sciences, 2016)
Mesial temporal sclerosis is closely related to temporal lobe epilepsy, a type of partial (focal) epilepsy in which the seizure initiation point can be identified within the temporal lobe of the brain. Mesial temporal sclerosis is the loss of neurons and scarring of the deepest portion of the temporal lobe and is associated with certain brain injuries. We present a case of a 40year old male who was presented with generalized seizures and was diagnosed with mesial temporal sclerosis.